Sub-micrometer electrospray ionization emitter enables direct infusion native mass spectrometric analysis of proteins and protein-ligand complexes in NaCl, Tris-HCl buffer - Lim, Su Wei (Nanyang Technological University, 2024)
In conventional electrospray ionisation (ESI) native mass spectrometry (native MS), proteins and protein-ligand complexes can be identified in minute amounts in a matter of minutes. To stabilize the native structures of proteins and protein-ligand complexes during analysis, salts and non-volatile molecules are a necessary addition in buffers. However, they tend to form adducts with analyte ions, increase background chemical noise and reduce signal-to-noise (S/N) ratios in mass spectral data. To circumvent this, sub-micrometer emitters were used instead of conventional microemitters for nano-electrospray ionisation (nano-ESI). Salt adduction was significantly lowered, resulting in increased peak resolution. An electrospray system was also assembled involving a syringe pump and a side electrical connection. This study thus suggests the increased effectiveness of sub-micrometer emitters in rapid identification of protein and protein-ligand complexes, especially in high salt, non volatile buffers.